(untitled) (American International Journal of Biology and Life Sciences, 2019)
In our past studies , some imine compounds were prepared m investigated , spectral characterization , it gave good evidence for formation these compounds , but in this studying , these imine derivatives were screened against some types of bacteria and microbes.